Java : a beginner's guide - Schildt, Herbert (McGraw-Hill Education, 2019)
"Fully updated for Java Platform, Standard Edition 11 (Java SE 11), Java: A Beginner's Guide, Eighth Edition gets you started programming in Java right away. Best-selling programming author Herb Schildt begins with the basics, such as how to create, compile, and run a Java program. He then moves on to the keywords, syntax, and constructs that form the core of the Java language. The book also covers some of Java's more advanced features, including multithreaded programming, generics, lambda expressions, modules, and Swing. As an added bonus, an introduction to JShell, Java's interactive programming tool, is included. Best of all, it's written in the clear, crisp, uncompromising style that has made Schildt the choice of millions worldwide"--